Does Reiki Benefit Mental Health Symptoms Above Placebo? - Zadro, Sonia; Stapleton, Peta (Frontiers in Psychology, 2022)
Background: Reiki is an energy healing technique or biofield therapy in which an attuned therapist places their hands on or near the client’s body and sends energy to the client to activate the body’s ability to heal itself and restore balance. It was developed in Japan at the end of the 19 th century by Mikao Usui of Kyoto. Given the enormous international socio-economic burden of mental health, inexpensive, safe, and evidenced based treatments would be welcomed. Reiki is safe, inexpensive and preliminary research suggests it may assist in treating a wide variety of illnesses. Given Reiki is a biofield therapy which is not yet accepted by the dominant biomedical paradigm, and its growing use, it is important to establish Reiki’s effectiveness over placebo. This study aimed to examine Reiki’s effectiveness over placebo in treating symptoms of mental health and to explore parameters for its effectiveness. Method: A systematic review of randomized placebo-controlled trials (RPCT) examining hands-on Reiki’s effectiveness in treating symptoms of mental health in adults was conducted through a systematic search of PubMed, PsycINFO, MEDLINE, CINAHL, Web of Science, Scopus, Embase, and ProQuest. Fourteen studies met inclusion criteria and the Risk of Bias was assessed using Cochrane‘s Revised ROB 2 assessment tool. This was followed by a GRADE assessment. Results: The evidence to date suggests Reiki consistently demonstrates a therapeutic effect above placebo for some symptoms of mental health. The GRADE level of evidence is high for clinically relevant levels of stress and depression, moderate to high for clinically relevant levels of anxiety, low to moderate for normal levels of stress and burnout, and low for normal levels of depression and anxiety. Conclusions: The results suggest Reiki may be effective in treating some areas of mental health over placebo. To date, there are a small number of studies in each area so findings are inconclusive and more RCT controlling for placebo in Reiki research is needed. Most studies were also assessed as having a risk of bias of some concerns. Incorporating Reiki as a complementary treatment to mainstream psychotherapy for depression, stress and anxiety may be appropriate.